Great Christian jurists in English history - Hill, Mark; Helmholz, Richard H. (Law and Christianity, 2017)
The Great Christian Jurists series comprises a library of national volumes of detailed biographies of leading jurists, judges and practitioners, assessing the impact of their Christian faith on the professional output of the individuals studied. Little has previously been written about the faith of the great judges who framed and developed the English common law over centuries, but this unique volume explores how their beliefs were reflected in their judicial functions. This comparative study, embracing ten centuries of English law, draws some remarkable conclusions as to how Christianity shaped the views of lawyers and judges. Adopting a long historical perspective, this volume also explores the lives of judges whose practice in or conception of law helped to shape the Church, its law or the articulation of its doctrine